Tathbiq Tiknulujiya Ta’lim Al Lughah Al Arabiyyah Mafhumuha Wa Wadhaifuha Wa Ahdafuha Wa Mabadiuha - Sahkholid Nasution (Arabic Education Program IAIN Pekalongan, 2017)
Arabic learning-like learning of other disciplines-requires technology as a systemic effort in designing, developing, implementing and evaluating the whole learning process. Through the application of tekonologi in learning Arabic is expected to be able to answer most of the problems experienced by teachers and students in learning Arabic, because technological learning techniques can help teachers in delivering materials and learners can also absorb the Arabic learning materials to the fullest. This paper is conceptual thinking using a descriptive-analysis method. The conclusion of this study is the application of technology in learning Arabic is an attempt to overcome the problematics of learning Arabic language. Because learning technology mengguanakan some principles, namely systemic approach (al madkhal al nizhamiy), student-oriented, and the use of learning resources to the fullest.